(untitled) (Academia Science Repository, 2023)
The article shows the simulation of the collision of particles of a dispersed mixture in pressure conduits. The phenomenon of particle collision is considered, which leads to the formulation of similarity requirements, which are difficult to fulfill in real conditions.